«CHURYUMOV UNIFIED NETWORK»: NEW, IMPORTANT TASKS FOR ASTRONOMICAL OBSERVATORIES TO PROTECT SOCIETY IN THE ERA OF MODERN HYBRID WARS - Churyumov, K. I.; Vidmachenko, A. P.; Steklov, A. F.; Dashkiev, N. G.; Romanyuk, Ya. O.; Stepakhno, I. V. (Одеські астрономічні публікації, 2016)
Authors created and provided the operation of the first version of the "Bolide Network of Churyumov" for continuous recording of twilight and daytime traces of aerial and aerospace intrusions overKievandKievdistrict during 2013-2016. Atotal of more than 36000 copyright photos was obtained, their classification was carried out and the first database was created. The authors recorded typical space invading meteoroids, comets nucleus fragments and traces of aerial intrusions, signs of which, as a rule, are observed at lower altitudes comparing with typical space invasions.